المحاكاة بين النظم الموسيقي والدلالة في قصيدة " أنشودة المطر " - بالقط, فريد (University of El-oued, 2021)
الملخص: إن التجربة الشعرية ذات البناء الموسيقي والصوتي لم توجد عبثا، فكل هذه البنى تحاكي قيمة دلالية معينة، وهذه المحاكاة لا تظهر بالوصف المباشر بين الشكل والمضمون، بل تتعلق بالقيمة الجمالية المستنبطة من كنه الشاعر، لأن البناء الصوتي عموما هو انعكاس للصدى الذي يجيش في نفس الشاعر، وفي هذا البحث محاولة للربط بين البنية الموسيقية والصوتية وبين القيمة الدلالة كمقاربة تصف الانسجام بينهما. Abstract Certainly, the poetic structure with its musical and phonological composition never existed in futility, as all these structures simulate a specific connotative significance. Important to note, this simulation does not occur in the straight description the takes place between form and content, but rather relates to the aesthetic value inferred from the poet’s identity, because the phonemic structure in general is a reflection of the echo that floods in the poet’s soul. This paper attempts to connect the musical and vocal structure with the connotative value as an approach that defines the harmony existing between the two.
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج04. ع.02. جامعة الوادي
Keywords: محاكاة ; بناء م ; بناء ص ; قافية ; دلالة